2021
DOI: 10.3389/fonc.2021.603932
|View full text |Cite
|
Sign up to set email alerts
|

RBM10 Regulates Tumor Apoptosis, Proliferation, and Metastasis

Abstract: The RNA-binding motif protein 10 (RBM10) is involved in alternative splicing and modifies mRNA post-transcriptionally. RBM10 is abnormally expressed in the lung, breast, and colorectal cancer, female genital tumors, osteosarcoma, and other malignant tumors. It can inhibit proliferation, promote apoptosis, and inhibit invasion and metastasis. RBM10 has long been considered a tumor suppressor because it promotes apoptosis through the regulation of the MDM2-p53 negative feedback loop, Bcl-2, Bax, and other apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Moreover, because expression of the tumor suppressor p53 is inhibited, p53 cannot exert transcriptional activation effects in LUAD [ 6 ]. The stability and activation of p53 are mainly regulated by murine double minute 2 (MDM2), which is part of the MDM2–p53 feedback loop necessary for regulating apoptosis [ 7 ]. MDM2-interacting proteins, including ribosomal proteins (RPs) [ 8 ] and Numb [ 9 ], also regulate p53 activation through their association with MDM2.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because expression of the tumor suppressor p53 is inhibited, p53 cannot exert transcriptional activation effects in LUAD [ 6 ]. The stability and activation of p53 are mainly regulated by murine double minute 2 (MDM2), which is part of the MDM2–p53 feedback loop necessary for regulating apoptosis [ 7 ]. MDM2-interacting proteins, including ribosomal proteins (RPs) [ 8 ] and Numb [ 9 ], also regulate p53 activation through their association with MDM2.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Some recent studies demonstrated that the expression level of RBM10 was associated with the regulation of cancer proliferation and metastasis. 12 Some studies in various cancer types suggest that RBM10 may act as a tumor suppressor. 13–15 However, the role of RBM10 in HCC remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…RBM10 is very highly correlated with the Bax expression which is the key gene in the apoptosis pathway in breast cancer. It is also positively correlated with p53 expression (38). An abnormal PALB2 gene results in a higher risk of breast cancer.…”
Section: Discussionmentioning
confidence: 94%